THE QUALITY OF COCONUT VINEGAR PRODUCED BY SLOW METHODS - Echy Warna Priasty; Hasanuddin Hasanuddin; Kurnia Herlina Dewi (BPFP Faperta UNIB, 2013)
The vinegar production needs two steps, the sugar changing to alcohol by yeast and then alcohol changing to vinegar by acetic acid bacteria. The vinegar could be produce by slow methods. The purposed of this study were to determine the influence of yeast and sugar using against the quality of fermentation result in first step (anaerobic), analyzing the influence of fermentation time against the vinegar quality based on SNI 01-3711-1995, and study the influence of fermentation time against the acetic acid content in second step (aerobic) with slow methods. This research used completely randomized design, the adding sugar (3 level) and yeast (3 level) as treatment. Each treatment was repeated three times. While the observation of vinegar quality used experiment research without the difference of treatment and repetition, used single error design. Result of research showed that vinegar quality have been suitable with SNI 01-3711-1995 about vinegar, include form, smell, acetic acid content, formic acid and oxalic acid. If the fermentation time be longer, the acetic acid content be lower in aerobic fermentation with slow methods, it was showed by the exponential regression formula ?= 20,695e-0,088x.